Habilidades sociais e de enfrentamento no tratamento de usuários de crack - Coelho, Leda Rúbia Maurina (2016)
This thesis describes the development and evaluation of the effects of a coping and social skills training – CSST program for people who use crack, using as an intervention approach the Relapse Prevention Model. Initially the theoretical and practical contexts of the research are presented, addressing the issues that this thesis set out to answer. To clarify these questions the thesis was structured in three sections. In the first section, the mixed design study aimed to investigate the coping skills and strategies of individuals who use crack. Participants had a lower middle repertoire in the “Inventário de Habilidades de Enfrentamento Antecipatório para a Abstinência de Álcool e outras Drogas – IDHEA-AD” and from transcripts of the interviews were created four categories: "Coping skills and plans for risk situations", "Expression of feelings," "Emotional self-control" and "Avoidance strategies". The description of social skills repertoire, anticipatory coping skills and self-efficacy of crack users before, immediately after completion of the training program and after three months is presented in section II. The findings of this quasi-experimental study demonstrated that participants had higher self-efficacy CSST scores for maintaining abstinence afterwards intervention. As for the overall IDEA-AD scores and the factors 1 - "Assertiveness and planning for high-risk situations and substance consumption" and 2 - "Emotional expression of positive feelings for abstinence maintenance" presented themselves lower middle before CSST as repertoire below average at the end of the intervention, and in-depth repertoire above average after three months. For the factor 3 scores - "Emotional self-control in adverse situations" participants had a good repertoire of coping skills in the initial assessment, increasing to in-depth repertoire in the post-CSST and thus remaining at follow-up. In analysis of overall scores and IHS-Del-Prette factors participants retained the measures unchanged during the pursuance, presenting a good repertoire of social skills. In section III predictive factors in crack withdrawal were studied. In this prospective investigation the following variables were considered as predictive of abstinence: be working in the initial assessment, improved performance in block design and digit span WAIS-III subtests, higher grades in IDHEA-AD final score, and especially in Factor 1, which refers to the assertive coping skills and plans for drug use risk situations. Variables gender, age, be studying, education, family income, as well as symptoms of depression, anxiety and stress, self-efficacy for abstinence from illicit drugs and participation in CSST program did not predict crack withdrawal.